OPTIMIZATION PARAMETERS OF COMPOSITE MATERIALS FOR THERMOFORMING MOLD USING THE DESIGN OF EXPERIMENT - Surekhum, Weerayut; Amdee, Noppadol; Sangsongfa, Adisak (Life Sciences and Environment Journal, 2024)
This research aimed to evaluate composite material design using precise engineering experiment principles called the design of experiment, employing the 2k full factorial test method to determine optimal mixes of natural and synthetic materials. Natural materials included ash powder, pineapple fiber powder, and sugar cane leaf fiber powder, while synthetic materials included aluminum, resin, cobalt, and resin hardener. The study utilized technical processes and experimental design methods to analyze and identify suitable composite materials. The statistical analysis demonstrated the precision of the experimental design by determining the optimum values of thermoforming molds, explicitly analyzing the Shore D hardness level compared to ASTM D2240 standards. The findings revealed that natural materials could effectively replace synthetic materials in the plastic molding industry. All factors expected to influence the Shore D value in the composite material were tested, yielding a hardness value not lower than or close to 80.00 Shore D. The optimal composition as the optimization parameters were identified as 70% resin, 0.01% cobalt, 2.0% hardener, and 20% aluminum powder, with a setting time of 18 hours and a temperature of 70°C. The response optimization method indicated a Shore D value of 80.6725, with experimental results closely aligning with these findings. The analysis showed an R-squared coefficient of 83.72%, confirming that adjusting factor levels according to the experimental design can significantly enhance the performance of composite materials in the thermoforming molding industry.